INCREASE OF THE TRAINING MATERIAL UNDERSTANDING LEVEL IN MATHEMATICS TRAINING OF STUDENTS - Tatyana P. Pushkaryeva (Открытое образование (Москва))
The work presents description of justification and research of ways of increase of understanding level of mathematical information in training of Pedagogical University students. The understanding model, its measuring instruments, and mathematics tutorial tools, which enforce its understanding level are offered.